Central African Economic and Monetary Community : A New Medium-Term Approach - de Zamaroczy, Mario; Fleuriet, Vincent; Gijon, Jose. (Washington, D.C. : International Monetary Fund, 2018)
This paper discusses possible reserve management approaches in the Central African Economic and Monetary Community (CEMAC). The paper looks beyond the region's current oil crisis and proposes a new approach to international reserve management in the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet